Polymyxin Combinations: Pharmacokinetics and Pharmacodynamics for Rationale Use. Issue 1 (January 2015) - Bergen, Phillip J.; Bulman, Zackery P.; Saju, Sarith; Bulitta, Juergen B.; Landersdorfer, Cornelia; Forrest, Alan; Li, Jian; Nation, Roger L.; Tsuji, Brian T.
<x xml:space="preserve">Abstract</x> Since their reintroduction into the clinic in the 1980s, the polymyxin antibiotics colistin—administered intravenously as an inactive prodrug, colistin methanesulfonate (CMS)—and polymyxin B have assumed an important role as salvage therapy for otherwise untreatable gram‐negative infections. However, the emerging pharmacodynamic and pharmacokinetic data on CMS/colistin and polymyxin B indicate that polymyxin monotherapy is unlikely to generate plasma concentrations that are reliably efficacious. Additionally, regrowth and the emergence of resistance with monotherapy are commonly reported even when concentrations exceed those achieved clinically. Given this situation, polymyxin combination therapy, which is increasingly being used clinically, has been suggested as a possible means of increasing antimicrobial activity and reducing the development of resistance. Although considerable in vitro data support this view, investigations of polymyxin combination therapy in patients have only recently commenced. The currently available clinical data for polymyxin combinations are generally limited to retrospective analyses and small, low‐powered, prospective studies using traditional dosage regimens that achieve low plasma concentrations. Considering the potential for rapid development of resistance to polymyxins, well‐designed clinical trials that include higher‐dose polymyxin regimens are urgently required to provide a more definitive answer regarding the role of polymyxin combination therapy compared with monotherapy. In this article, we provide an overview of key in vitro and clinical investigations examining CMS/colistin and polymyxin B combination therapy.